Brief Report: Bullying and Anxiety in High-Functioning Adolescents with ASD - van Schalkwyk, Gerrit; Smith, Isaac C.; Silverman, Wendy K.; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Youth with ASD are more likely to experience bullying than their typically developing peers. This risk has not been studied in youth with ASD transitioning to college. We examined the occurrence of bullying in 35 high functioning youth with ASD who were preparing to attend college. We also examined youth anxiety and ASD symptoms. Fifty-one percent of the sample reported being recent victims of bullying; 31% of parents reported their child was a victim of bullying. Parent report of bullying correlated significantly with ratings of youth social anxiety symptoms. These findings suggest that bullying is an issue of concern for higher functioning, older adolescents with ASD, and that their own reports may be particularly important in identifying its occurrence.
Keywords: Anxiety; Autism spectrum disorder; Bullying; Postsecondary education; dept.sed